THE ROLE OF FREIGHT FORWARDERS IN IMPORT-EXPORT SERVICES(Case Study of PT. Sinotrans CSC Indonesia) - Kencana Verawati; Mohammad Naufal Abdullah, Arnold Habibie, Ziqra Maulana Zulmarjon, Sultan Sai’d Al Takhir Pasyah (Adisam Publisher, 2024)
Logistics is a series of efforts that cover the effectiveness, planning, implementation, and supervision of a process of moving goods or services, energy, or other resources, from the starting point to the user point. Every company, in any form or field, especially in the field of commerce, cannot run properly to make a profit without the means of transportation (Hasibuan et al., 2021), This research method, some experts call it the positivistic method because it is based on the philosophy of positivism, Observation is a way to obtain information from an event through direct observation & Interview: a